Assessing the Impact of Intelligence Tests on College Students' Motivation to Learn in Increasing Self-Awareness - M. Bagas Putra Pratama; Raul Rian Shaputra; M. Handi Pratama; Alrefi Alrefi (Sriwijaya University Learning and Education International Journal, 2025)
This study uses a qualitative method with a phenomenological approach to examine objects directly using descriptive questions on interview participants and without the use of numerical instruments. The purpose of this research is to find out the experience of parsipan after conducting intelligence tests on increasing motivation in learning. Data obtained through interviews with four female students of the Guidance and Counseling study program at the Faculty of Teacher Training and Education, Sriwijaya University. The results of this study state that when doing the test tends to feel tired, anxious and there is pressure or pressure in doing the test and it is hoped that when going to take the test participants can better maintain expectations on the results that will be obtainedh.